Estrés en las relaciones interpersonales en los jóvenes voluntarios de la Asociación Jóvenes Revolucionarios al Mando de Babahoyo (J.R.M.B) de la Ciudad de Babahoyo - Macías Lemus, Jorge Antonio (2017)
This research aims to improve the activities of interpersonal relationships, so you can talk to your friends but not write in a scientific document that causes stress because of the different actions that youths develop in the Association of Young Revolutionary Babahoyo Command. In which it is put in consideration that the main objective is the one to be related between the different relatives and friends with the purpose of reaching the change in the different young people. The exercises and activities contained in the games to relieve stress, are directed at everyone, from office workers sedentary and asphyxiated by the time to executives under great stress. They help to mitigate situations of high pressure at home and at work with relaxation exercises, which also include life planning and organization activities to combat stress, can be carried out individually or in groups and most can be done in less than 5 minutes. Stress comes from physics and architecture and refers to the force that is applied to an object, which can deform or break it. In psychology, stress usually refers to certain events in which we encounter situations that involve strong demands for the individual, who can exhaust their coping resources. At present, in the last years it is accepted as the most complete. Thus, stress is thought to occur as a result of an imbalance between the demands of the environment (internal or external stressors) and the available resources of the subject. In social acceptance it is important to know the role played by Emotional Intelligence in each of the young people through Social Skills which will allow establishing the lines of action in intervention programs with socially vulnerable adolescents in each of the stages that are Find problems in interpersonal relationships appear when we lack social skills, we have problems of self-control such as anger, aggression or we feel insecure and undervalued